Epidermolysis bullosa in Finland : clinical features, morphology and relation to collagen metabolism - Kero, Matti (Oulu ; [Stockholm] : [M. Kero] : [Almqvist & Wiksell, distr.], 1984)
Abstract.
6 excerpts.
Nimiösivulla myös: From the Department of Dermatology, University of Oulu, Finland.
Artikkeliväitöskirjan yhteenveto-osa ja 6 eripainosta.
Tiivistelmä myös erillisenä.
Väitösk. lisäksi 1 irtol.
Väitöskirja
Keywords: epidermolysis bullosa; Epidermolysis Bullosa -- genetics; Finland; mechanobullous diseases; histology of EB; collagen metabolism; Academic Dissertation; väitöskirjat; doktorsavhandlingar